Role of NLRP3 inflammasome and oxidative stress in hepatic insulin resistance and the ameliorative effect of phytochemical intervention - de Deus, Isabela Jesus; Martins-Silva, Ana Flávia; Fagundes, Miliane Martins de Andrade; Paula-Gomes, Sílvia; Silva, Fernanda Guimarães Drummond e; da Cruz, Larissa Leandro; Abreu, Aline Rezende Ribeiro de; de Queiroz, Karina Barbosa (Frontiers in Pharmacology, 2023)
NLRP3 inflammasome has a key role in chronic low-grade metabolic inflammation, and its excessive activation may contribute to the beginning and progression of several diseases, including hepatic insulin resistance (hIR). Thus, this review aims to highlight the role of NLRP3 inflammasome and oxidative stress in the development of hIR and evidence related to phytochemical intervention in this context. In this review, we will address the hIR pathogenesis related to reactive oxygen species (ROS) production mechanisms, involving oxidized mitochondrial DNA (ox-mtDNA) and thioredoxin interacting protein (TXNIP) induction in the NLRP3 inflammasome activation. Moreover, we discuss the inhibitory effect of bioactive compounds on the insulin signaling pathway, and the role of microRNAs (miRNAs) in the phytochemical target regulatory mechanism in ameliorating hIR. Although most of the research in the field has been focused on evaluating the inhibitory effect of phytochemicals on the NLRP3 inflammasome pathway, further investigation and clinical studies are required to provide insights into the mechanisms of action, and, thus, encourage the use of these bioactive compounds as an additional therapeutic strategy to improve hIR and correlated conditions.